Barzakh and the Imaginal Realm: A Phenomenology of Postmortem Experience in Sufism - Muhammad Valiyyul Haqq; Iskandar Arnel (Parahyangan Catholic University, 2025)
This study examines the phenomenology of barzakh in the corpus of classical Sufism as a model of liminal postmortem experience and analyzes its implications for afterlife concepts in other religious traditions. The aim of this research is to explain how Sufi thinkers—particularly Ibn ‘Arabi, Suhrawardī, and al-Jīlī—understand barzakh not as a static space of waiting but as an imaginal realm with its own ontological structure, experienced through the imaginal consciousness of the human being. Employing a qualitative design grounded in narrative-phenomenological analysis, this study conducts an in-depth textual examination of Sufi works and interprets their imaginal narratives as manifestations of transformative consciousness. The findings reveal three main points. First, barzakh is conceived as an ontological imaginal reality in which the subtle body, liminal space, and postmortem forms manifest through al-khayāl al-muttaṣil as the medium of the soul’s experience. Second, barzakh functions as a moral mirror in which one’s deeds, intentions, and inner states become objectified into imaginal landscapes directly encountered by the soul, thereby dynamically shaping its postmortem existential environment. Third, the comparative analysis demonstrates structural parallels between the phenomenology of barzakh and intermediate-realm concepts in non-Islamic traditions—such as Bardo Thodol in Tibetan Buddhism and Olam Ha-Ba in Judaism—which similarly exhibit liminal experiential patterns involving transformations of consciousness, the subtle body, guidance by transcendent entities, and reflective imaginal spaces. This study contributes to the expansion of esoteric Sufi studies by employing a phenomenological approach that interprets barzakh as a structure of experience rather than merely a theological doctrine. Moreover, it offers a new hermeneutical framework for interreligious dialogue by highlighting shared patterns of transitional consciousness across afterlife traditions. The originality of this research lies in its integration of phenomenological analysis with comparative afterlife studies, demonstrating barzakh as a universal archetype of transformative human experience.